12x+4=9x-23

Simple and best practice solution for 12x+4=9x-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12x+4=9x-23 equation:


Simplifying
12x + 4 = 9x + -23

Reorder the terms:
4 + 12x = 9x + -23

Reorder the terms:
4 + 12x = -23 + 9x

Solving
4 + 12x = -23 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
4 + 12x + -9x = -23 + 9x + -9x

Combine like terms: 12x + -9x = 3x
4 + 3x = -23 + 9x + -9x

Combine like terms: 9x + -9x = 0
4 + 3x = -23 + 0
4 + 3x = -23

Add '-4' to each side of the equation.
4 + -4 + 3x = -23 + -4

Combine like terms: 4 + -4 = 0
0 + 3x = -23 + -4
3x = -23 + -4

Combine like terms: -23 + -4 = -27
3x = -27

Divide each side by '3'.
x = -9

Simplifying
x = -9

See similar equations:

| 6n=18-2n | | 0.25x+0.4y-1=0 | | 19.50x=2500. | | 8(-1-3p)-5= | | 6+x=-24 | | x/2-x/3=8 | | p-11=-9+p | | 0=1.3v+1 | | 6(4x-5)(4x+3)=0 | | 2-7(x+1)=3(x-2)-5(x+3) | | 756x^18= | | (3x+8)=(5x-2) | | y-1=.5x-7 | | 5x+2=4x+2 | | 7(5+n)=42 | | 45x-37y+87-7+3x= | | 12x=29.9 | | 2y-8=y+4 | | 5n+n=3n-2+2(2n+1) | | 2+8lnx=26 | | 24.4-4p=53.3 | | 15+3x+6=-7x+2x+2 | | 12r^2+21r-8r-14=0 | | 2x+2=-5x+23 | | 6x+11=2x+47 | | 16a+3= | | y-5=0x-7 | | p(x)=[x-(1+2i)][x-(1-2i)](x-2)(x+1) | | 3xy+7x+6x+8xy= | | p=-12.5t+100 | | 0.5y+0.2y=0.3y+2 | | 13-1(2x+4)=35 |

Equations solver categories